2021
DOI: 10.1042/cs20210476
|View full text |Cite
|
Sign up to set email alerts
|

NELL2 modulates cell proliferation and apoptosis via ERK pathway in the development of benign prostatic hyperplasia

Abstract: Benign prostatic hyperplasia (BPH) is a quite common illness but its etiology and mechanism remain unclear. Neural epidermal growth factor-like like 2 (NELL2) plays multifunctional roles in neural cell growth and is strongly linked to the urinary tract disease. Current study aims to determine the expression, functional activities and underlying mechanism of NELL2 in BPH. Human prostate cell lines and tissues from normal human and BPH patients were utilized. Immunohistochemical staining, immunofluorescent stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…A particularly high expression of NELL2 was detected in NSCs that were apically located within the neural rosettes compared to cells positioned close to the basal level, and this was confirmed by confocal imaging of human neural rosettes double labelled with NelL2 and ZO1 antibodies ( Figure 3E ). These data are consistent with previous studies in human cell lines and rats that indicated Nell2 modulates cell proliferation and growth ( Kim et al, 2020 ; Liu et al, 2021 ). Since human iPSC-derived cortical brain organoids contain both mature neurons and glia, we next analyzed the expression of NELL2 in these cell types in 8- and 10-week-old brain organoids by co-staining with NEUN for neurons, GFAP for astrocytes, and CNPase for oligodendrocytes.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A particularly high expression of NELL2 was detected in NSCs that were apically located within the neural rosettes compared to cells positioned close to the basal level, and this was confirmed by confocal imaging of human neural rosettes double labelled with NelL2 and ZO1 antibodies ( Figure 3E ). These data are consistent with previous studies in human cell lines and rats that indicated Nell2 modulates cell proliferation and growth ( Kim et al, 2020 ; Liu et al, 2021 ). Since human iPSC-derived cortical brain organoids contain both mature neurons and glia, we next analyzed the expression of NELL2 in these cell types in 8- and 10-week-old brain organoids by co-staining with NEUN for neurons, GFAP for astrocytes, and CNPase for oligodendrocytes.…”
Section: Resultssupporting
confidence: 93%
“…Our confocal 3D reconstruction imaging of the human rosettes strongly suggests Nell2 is intracellular (Figure 3E). Collectively, these data suggest that NELL2 may regulate the proliferation of rNSCs during development, in line with previous studies (Aihara et al, 2003;Nelson et al, 2004;Jeong et al, 2008) that demonstrated that NELL2 modulates cell proliferation and growth in human and rat cells (Kim et al, 2020;Liu et al, 2021). We certainly detected consistent differences in expression levels between rNSC and cNSC populations.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, PMA treatment stimulated PPE-Luc, while co-transfection of either NELL2 expression vectors or NELL2 expression vectors + BFA inhibited PMA-induced PPE-Luc activity. Given that NELL2 is known to be related to ERK activation ( Aihara et al, 2003 ; Choi et al, 2010 ; Kim et al, 2014 ; 2015 ; Liu et al, 2021 ), one of the multiple downstream pathways of PKC signaling, we next examined the involvement of ER-localized NELL2 in the activity of ERK, as represented by level of phosphorylated ERK (pERK). In western blot analyses, pERK was undetectable in control NIH3T3 cells, but was induced strongly by PMA treatment ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For cell apoptosis analysis, a FITC Annexin V Apoptosis Detection Kit I (BD Biosciences, USA) was used. BPH-1, WPMY-1, and RWPE-1 cells (1 × 10 6 cells) were harvested and then stained with the FITC Annexin V Apoptosis Detection Kit I reagents according to the manufacturer's instructions [ 21 ].…”
Section: Methodsmentioning
confidence: 99%